Collaborators for emancipation : Abraham Lincoln and Owen Lovejoy - Moore, William F. (William Frederick), 1935- (University of Illinois Press, 2014)
Few expected politician Abraham Lincoln and Congregational minister Owen Lovejoy to be friends when they met in 1854. One was a cautious lawyer who deplored abolitionists' flouting of the law, the other an outspoken antislavery activist who captained a stop on the Underground Railroad. Yet the two built a relationship that, in Lincoln's words, 'was one of increasing respect and esteem'. In 'Collaborators for Emancipation', the authors examine the thorny issue of the pragmatism typically ascribed to Lincoln versus the radicalism of Lovejoy, and the role each played in ending slavery.